2022
DOI: 10.1007/s12928-022-00836-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of door-to-balloon time and in-hospital outcomes in patients with ST-elevation myocardial infarction between before versus after COVID-19 pandemic

Abstract: The situation around primary percutaneous coronary intervention (PCI) has dramatically changed since coronavirus disease 2019 (COVID-19) pandemic. The impact of COVID-19 pandemic on clinical outcomes as well as door-to-balloon time (DTBT), which is known as one of the indicators of early reperfusion, has not been fully investigated in patients with ST-elevation acute myocardial infarction (STEMI). The purpose of this study was to compare DTBT and in-hospital outcomes in patients with STEMI between before versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In the present study, the DTBT was significantly longer and 180-day mortality numerically (but not significantly) greater in the after-pandemic period than the pre-pandemic period, which was consistent with the previous Japanese reports [ 3 5 ]. On the other hand, the results outside of Japan have shown an increase in the mortality from AMIs in the after-pandemic period [ 18 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the DTBT was significantly longer and 180-day mortality numerically (but not significantly) greater in the after-pandemic period than the pre-pandemic period, which was consistent with the previous Japanese reports [ 3 5 ]. On the other hand, the results outside of Japan have shown an increase in the mortality from AMIs in the after-pandemic period [ 18 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies from Japan have reported a significantly longer time of the door-to-balloon time (DTBT), while the short-term mortality has been preserved after the COVID-19 pandemic as compared to that before the pandemic in patients with ST-elevation myocardial infarctions (STEMIs) [ 3 5 ]. As for the patients with non-ST-elevation myocardial infarctions (NSTEMIs), there are few Japanese data focusing on investigating the impact of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear why AMI workflow was significantly disrupted with prolonged S2DT and D2BT in the COVID-19 group. Through literature review, we identified many studies with findings in line with our study results (prolongation of pre-hospital and in-hospital delay) [15,17,23]. Although not specified in the data of the present study, the EMS pro- cess time may be prolonged during the COVID-19 pandemic era because of safety precautions and changes in basic preparatory procedure [9,24,25].…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, little is known about the clinical characteristics and treatment outcomes of ST-segment elevation myocardial infarction (STEMI), which requires timely and rapid percutaneous coronary intervention (PCI), in South Korea between pre-COVID-19 and COVID-19 periods. In particular, the treatment delay for STEMI was expected in the COVID-19 era, and this has been supported by clinical evidence in several studies [15][16][17]. Therefore, we aimed to analyze the differences in the clinical characteristics and treatment outcomes before and after the COVID-19 era in patients with STEMI in South Korea.…”
Section: Introductionmentioning
confidence: 87%
“…Studies from Emilia-Romagna [ 57 ] and Lombardia [ 43 ] have found an increase in out-of-hospital mortality due to cardiac causes in the first wave of the pandemic. While Tuscany was relatively less affected by COVID-19 compared to other regions in Italy, complementary studies that examine cardiac conditions care pathway process measures such as door-to-balloon time [ 58 ] can better elucidate interpretations. For example, Rossi and colleagues found that in-hospital mortality rates for AMI patients did not change significantly after COVID-19 in Brescia despite an increase in door-to-balloon time, pointing towards a threshold of care management of keeping this measure to 95 min for AMI patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%